Mechanical and aerospace engineering V : Selected, peer reviewed papers from the 2014 5th International Conference on Mechanical and Aerospace Engineering (ICMAE 2014), July 18-19, 2014, Madrid, Spain - Hoxha, Dashnor; Rivera, Francisco; McAndrew, Ian (Advanced materials research, 2014)
Collection of selected, peer reviewed papers from the 2014 5th International Conference on Mechanical and Aerospace Engineering (ICMAE 2014), July 18-19, 2014, Madrid, Spain. The 146 papers are grouped as follows: Chapter 1. Applied Mechanics and Manufacturing, Chapter 2. Dynamics, Vibration and Acoustics Analysis, Chapter 3. Material Characterisation and Technology, Chapter 4. Aerodynamics, Aeroengineering and Aerospatial Applications, Chapter 5. Fluid Dynamics and CFD Application, Chapter 6. Motors and Engines, Combustion and Propulsion, Chapter 7. Control Systems, Robotics and Automatics, Chapter 8. Thermal Analysis Technologies and Applications, Chapter 9. Computational Techniques and Numerical Methods Keyword: Applied Mechanics and Manufacturing, Dynamics, Vibration and Acoustics Analysis, Material Characterisation, Aerodynamics, Aeroengineering, Fluid Dynamics, Motors and Engines, Control Systems, Robotics and Automatics, Thermal Analysis, Computational Techniques and Numerical Methods Nearly 150 papers cover applied mechanics and manufacturing; dynamics, vibration, and acoustic analysis; material characterization and technology; aerodynamics, aero-engineering, and aerospace applications; fluid dynamics and applications of computational fluid dynamics; motors and engines, combustion, and propulsion; control systems, robotics, and automatics; thermal analysis technologies and applications; and computational techniques and numerical methods. Among specific topics are characterizing the dynamics of missiles with control flaps using computational fluid dynamics, static and dynamic tensile behavior in unidirectional glass-epoxy composites, investigating and simulating a supersonic gas jet for removing Martian dust, and calculating heat transfer in heterogeneous structures such as a honeycomb with the numerical solution of stochastic differential equations. -- Aerospace engineering-- Materials science-- Mechanical engineering.